THU0519 Tissue Factor Over-Expression Identify Patients with Rheumatic Diseases. (10th June 2014) - Maugeri, N.; Canti, V.; Baldini, M.; Rovere-Querini, P.; Baldissera, E.; Sabbadini, M.G.; Manfredi, A.
Abstract : Background: Premature coronary heart disease and thromboembolic complications have emerged as a major cause of morbidity and mortality in patients with autoimmune rheumatic diseases. Tissue factor (TF) is a pivotal signal within the coagulation cascade that results in the thrombin generation. In turn thrombin, besides its well-characterized role as an effector of clot formation, is also a potent signal driving the activation of platelets and endothelial cells. An elevated incidence of thromboembolic events has been reported in patients with autoimmune diseases. Objectives: We analyzed the TF expression on blood cells in patients with autoimmune diseases and matched healthy controls. Methods: We studied a group of twelve active rheumatic patients comprising 8 females and 4 males, 45 (24-65) years old. Four patients had with reactive arthritis, two with Adult Still's disease (AOSD), three with ankylosing spondylitis (SA) and three with rheumatoid arthritis (RA). We compared results with 14 healthy donors, sex (8 female and 6 male) and age (median 47, range 27-65 years old) – matched. TF expression was analyzed in platelets, monocytes and neutrophils by flow cytometry in whole blood samples. Results are expressed as mean ± SEM. Results: A strikingly higher fraction of patients blood cells expressed TF compared to healthy controls. Specifically, platelets expressing TF were the 23.6±2.0 in patients vs. 2.5±0.7% in controls. The monocyte TF expression was 19.2±4.0 in patients vs. 1.9±0.6% in controls and neutrophil TF expression was 22.3±3.3 in patients vs. 2.4±1.1% in controls. All p <0.001. We did not observe any significant association between blood cell TF expression and age, sex, actual diagnosis, disease duration or treatment. Conclusions: The fraction of TF positive leukocytes and platelets was consistently higher in patients with rheumatic diseases compared with matched controls. This features is shared by patients with diseases with different pathogenesis and clinical features, such as AR, SA and AOSD. This feature could be involved in the increased thromboembolic risk associated to rheumatic conditions. References: Maugeri N. et al; Srp Arh Celok Lek. 2010. Maugeri N. et al; Autoimmunity 2009. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5071